Prevention of Sudden Cardiac Death (SCD) Possible Strategies - Safiuddin, Mohammad (University Heart Journal, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/uhj.v8i2.16090 University Heart Journal Vol. 8, No. 2, July 2012